A COMUNICAÇÃO DE MERCADO A SERVIÇO DA IGREJA Em busca da fidelização - Gusso, Ana Cláudia (2008)
This research brings into evidence both the use of internal, directed communication instruments and the use of public relations actions and relationship marketing inside the historic evangelical churches. The aim is to check if those instruments have any relation to the loss or retention of members in those churches and in their numerical growth in the face of a new religious configuration, where fidelity is getting harder to get every day. This study emphasizes the importance of internal communication and marketing communi cation strategies used inside the historic churches as an aid to the so called word of mouth marketing. In order to do this research, an analysis of the four historic churches in Curitiba with the greatest number of members was conducted. Those churches are the Baptist, the Lutheran, the Presbyterian and the Methodist. The study was carried on by participating observation research, analysis of various kinds of materials, interviews with church leaders and a quantitative research which involved the members and the visitors of the four churches. By using a structured questionnaire, this study analyzed the behavior of these members face to the internal directed communication means used in the churches and the relationships that happen inside them, both between their members and between the members and their leaders.(AU)